5Ps STRATEGY FOR COAL MINING GOVERNANCE IN THE PERSPECTIIVE OF SDGs IN SOUTH MALINAU, NORTH KALIMANTAN - Labo, Tomy; Setyowati, Endah; Domai, Tjahjanulin (The International Journal of Accounting and Business Society, 2019)
AbstractÂ The objective of the study is to construct 5Ps strategy for coal mining governance using the perspective of SDGs in the Malinau District of North Kalimantan, Indonesia. The study was conducted using qualitative method. Data was collected through field observations and in-depth interviews, and secondary data of official published documents. Data was analyzed using the interactive analysis Model of Mile, Huberman, and Saldana. This research concluded that the 5Ps strategy for coal mining productions in the Malinau District of North Kalimantan is very useful for governing all stakeholders in the District in respect to environmental, social and economic aspects. The 5Ps strategy is 1) People, this means communities should be involved in the coal mining governance, 2) Planet, environmental awareness, 3) Profit, economic aspects should be well calculated and managed, 4) Peace, justice and equality are also the spirit to manage the coal productions and colaborations among the stakeholders are important to make the success of production.Keywords: Coal Mining Governance, Sustainable Development Goals, 5Ps Strategy